Development of stimuli-responsive smart hydrogels using molecular imprinting and interpenetrating polymer networks - Oliveira, Tânia (2014)
Different classes of stimuli-responsive smart hydrogels (SRSH) were synthesized in order to assess the usefulness of molecular imprinting and generation of interpenetrating polymer networks to obtain advanced materials with tailored properties/performance. Reversible Addition-Fragmentation Chain-Transfer (RAFT) polymerisation was exploited as an additional tool to increase the control on the formation process of these materials. Batch adsorption and frontal analysis (e.g. for 3-aminopyridine (3AMP) as depicted in the graphical abstract) techniques were used to quantify the affinity of different drugs with the produced SRSH. Stimulated drug release (e.g. due to temperature/pH changes) and protein immobilisation/release were also tested. Results obtained show that molecular imprinting and generation of interpenetrating networks are effective routes to obtain tailored materials with a particular affinity to selected template molecules.